Assessment and outcome of open fracture treatments [clinico-radiological evaluation, bacteriological findings and gait analysis] in dogs and cats presented to University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) - Mohd Arip, Erni Wati (2014)
Total of 27 dogs and cats presented to UVH-UPM between early of September 2013 until end of April 2014 for open fracture treatments were studied prospectively. Out of 27 patients, 92.6% (25/27) were cats and only 7.4% (2/27) were dogs. This could be due the fact that cats were free-roamers (55.6%) and relatively being more exposed to accidents. Almost half of open fractures were due to traumatic injuries with fell down from high storey building (25.9%) and road traffic accidents (14.8%). Young patients (less than 2 years old) seemed to be particularly at risk with higher number of cases presented at that age group. In this study, we found that 48.1 % (13/27) of patients had tibial fractures, 14.8% (4/27) digital fractures or disarticulation, 14.8% (4127) femoral fractures, 14.8% (4127) radial fractures and 3.7% (1/27) humeral fractures. Six patients (22.2%) carne with extensive skin and tissue damage at the fracture site (Grade III), fourteen patients with Grade II and seven patients with Grade I. Bacterial culture and antibiotic sensitivity test performed in 17 patients revealed presence of 18 different types of bacteria including E.coli, Klebsiella pneumonia, Enterobacter aerogenes, Enterobacter cloacae, Enterobacter faecalis and Proteus mirabilis. Preanaesthetics screening showed that 47.6% had increase in Alanine transaminase (ALT) and 86.7% Creatinie Kinase (CK) of the blood parameters. External skeletal fixation (ESF) with trans articular pin was performed in 4 patients, ESF only in 4 patients, amputation in 4 patients and 4 patients were sent horne with splint bandage due to the owners' financial constraint. Radiographic findings showed callus formation started to develop within 4 weeks after surgical repair. Gait analyses were performed only on 9 patients due to owners' poor compliances post-surgery. Analysis showed only four could use the affected limbs normally with good bone alignment, satisfactory outcome in one patient showed weight bearing lameness with some degree of misalignment, unsatisfactory in three patients and one patient still under monitoring.